2017
DOI: 10.1016/j.tipsro.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of butylscopolamine in obtaining clear MR image for intensity-modulated radiotherapy for prostate cancer

Abstract: The use of butylscopolamine in magnetic resonance imaging (MRI) of the prostate is controversial in the context of diagnostic imaging where local invasion and the presence of metastases are evaluated. However, in radiation oncology, MRI is performed as part of the simulation process, and the objectives differ to the diagnostic setting. MRI is primarily used for accurate target delineation; hence, the use of an agent to reduce intestinal peristalsis and increase image quality may be beneficial. The impact of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was reported that repeat imaging after 29 min (mean) did not result in a significant deterioration in image quality. MR imaging of the abdominal region following butylscopolamine administration are of significantly superior quality (18,19). Additionally, Martı-Bonmatıé t al.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that repeat imaging after 29 min (mean) did not result in a significant deterioration in image quality. MR imaging of the abdominal region following butylscopolamine administration are of significantly superior quality (18,19). Additionally, Martı-Bonmatıé t al.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been mixed reports for MRI prostate cancer staging studies. Reports suggest image quality was independent of hyoscine butylbromide or that there was no significant effect of hyoscine butylbromide on the prostate's image quality the prostate 21,33 contrast with studies showing hyoscine butylbromide improved imaging quality of the pelvic organs and was recommended for good MRI images 22,34 . A recent European conference of radiologists came to no consensus on using IV hyoscine butylbromide for imaging of rectal cancer 35 …”
Section: Discussionmentioning
confidence: 99%